2015
DOI: 10.1371/journal.pone.0120573
|View full text |Cite
|
Sign up to set email alerts
|

Balance Impairment in Patients with COPD

Abstract: Background/PurposeChronic obstructive pulmonary disease (COPD) is a respiratory disease that results in progressive airflow limitation and respiratory distress. Physiopathological features of COPD suggest that people who suffer from this disease have many risk factors for falls that have been identified in older individuals. The aim of the study was to compare and quantify functional balance between COPD patients and healthy subjects; to investigate the risk of falls in acute stages of the disease and to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
4
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 37 publications
2
58
4
7
Order By: Relevance
“…COPD patients typically have many shared risk factors for falls, such as muscle weakness, mobility impairment, and exercise intolerance (Kim, Mofarrahi & Hussain, 2008; Ries et al, 2007). Compared with healthy controls, the presence of COPD has been shown to be associated with significantly impaired ability to perform balance tests, such as the Berg Balance Scale, timed up and go test, and single-leg stance (Crisan et al, 2015; Porto et al, 2015). An observational cohort study reported a high prevalence of previous falls in COPD patients (32%), with an incidence rate of 0.1 (95% CI [0.06–0.14]) falls/person-month (Roig et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…COPD patients typically have many shared risk factors for falls, such as muscle weakness, mobility impairment, and exercise intolerance (Kim, Mofarrahi & Hussain, 2008; Ries et al, 2007). Compared with healthy controls, the presence of COPD has been shown to be associated with significantly impaired ability to perform balance tests, such as the Berg Balance Scale, timed up and go test, and single-leg stance (Crisan et al, 2015; Porto et al, 2015). An observational cohort study reported a high prevalence of previous falls in COPD patients (32%), with an incidence rate of 0.1 (95% CI [0.06–0.14]) falls/person-month (Roig et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the adherence to treatment will decrease, especially to rehabilitation programs [19].…”
Section: Balance Disorders: Nosology Prevalence Clinical Consequencesmentioning
confidence: 99%
“…COPD patients typically have many shared risk factors for falls, such as muscle weakness, mobility impairment, and exercise intolerance (Kim et al 2008;Ries et al 2007). Compared with healthy controls, the presence of COPD has been shown to be associated with significantly impaired ability to perform balance tests, such as the Berg Balance Scale, timed up and go test, and single-leg stance (Crisan et al 2015;Porto et al 2015). An observational cohort study Manuscript to be reviewed reported a high prevalence of previous falls in COPD patients (32%), with an incidence rate of 0.1 (95% CI, 0.06-0.14) falls/person-month (Roig et al 2011).…”
Section: Discussionmentioning
confidence: 99%